Pre-service English Teachers’ Strategies in Incorporating Character Education during the Teaching Practice Program at UIN Antasari Banjarmasin - Asfihana, Raida (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This research explores the strategies performed by pre-service English teachers in incorporating traits or character in writing their lesson plans during their teaching practicum. Twelve students of the English Department at Universitas Islam Negeri Antasari Banjarmasin were recruited to join the study. This course explored the experience of undertaking an authentic teaching and learning activity of these pre-service English teachers, starting from creating a syllabus, writing lesson plans to execute a micro-teaching action. A classroom-based study is conducted to generate data. Primary data was obtained in the micro-teaching class through a participatory observation technique, in-depth interviews, and analysis of the lesson plan documents. The data were analyzed qualitatively using thematic analysis. The findings indicate that they mainly used instructional methods for group discussion and small group presentation. Honesty, trustworthiness, respect, and responsibility are the traits that are expressed in their lesson plans. Next, this study’s outcome is expected to increase teacher understanding of various possibilities in developing the lesson plans and instructional materials that facilitate the character-building incorporation.